Geochronology, petrogenesis, and tectonic setting of Late Triassic volcanic rocks of the Hadataolegai Formation, central Great Xing'an Range, Northeast China. (4th July 2018) - Tang, Zong‐Yuan; Sun, De‐You; Gou, Jun; Yang, Dong‐Guang
Abstract: In this study, new geochemical, zircon U–Pb, and Lu–Hf isotopic data are presented for volcanics from the Hadataolegai Formation of the central Great Xing'an Range (GXR) in Northeast China. These new data offer insights into the petrogenesis of the volcanics of the Hadataolegai Formation and the tectonic evolution of the Paleo–Asian Ocean (PAO) and Mongol–Okhotsk Ocean (MOO). These volcanics of the Hadataolegai Formation are divided into andesite‐trachyandesites and dacite‐trachydacites. Zircon U–Pb ages show that the volcanics of the Hadataolegai Formation erupted between 230 Ma and 228 Ma during the Late Triassic, which agrees with recently obtained data. The volcanic rocks in this study have low Y (9.9–21.1 ppm) and Yb (0.78–2.02 ppm) contents, high Sr (444–954 ppm) contents, and slight Eu anomalies (δEu = 0.82 to 0.94), similar to 'adakite‐like' rocks. The dacites were formed by fractional crystallization of coeval andesitic magmas. The zircons within the andesite and trachyandesite yield higher positive εHf (t) values (+6.3 to +12.0) and model ages (TDM2 ) between 860 Ma and 453 Ma, which indicates that the magmas were generated by a newly accreted continental crustal source. Moreover, some of the volcanics are relatively high in MgO contents. These characteristics indicate that the volcanic magmas were derived from the partial melting of delaminated lower crust and mixing with mantle materials. Combining these data with previous studies, we suggest that the magmatism in the central GXR was governed by extension due to the closure of the PAO and the back‐arc extension associated with the southward subduction of the MOO plate (western GXR, near the Erguna Block). Abstract : The volcanics of the Hadataolegai Formation in the central GXR erupted during the Late Triassic (235–226 Ma).The magma originated due to the partial melting of the delaminated lower crust and interaction with surrounding mantle material as the material ascended. The magmas underwent fractional crystallization prior to eruption.Late Triassic igneous rocks in the central GXR were dominated by post‐orogenic extension, which was related to extension after the closure of the PAO along the Hegenshan–Heihe suture belt, and the back‐arc extension, which was related to the MOO tectonic regime (especially near the EB).